Restructurisasi Kognitif dalam Penangan Kecemsan pada Ibu Rumah Tangga : Studi Kasus Klinis - Dewi Agustina Sari; Karolin Rista (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to examine the dynamics of anxiety in a housewife who experienced relational trauma as a result of spousal infidelity, as well as to evaluate the effectiveness of individual counseling using the Cognitive Restructuring technique. The research subject was Melati (a pseudonym), a housewife who exhibited symptoms of anxiety, depression, and stress following the infidelity incident. The methods employed included clinical interviews, observation, and the use of psychological assessment instruments, namely the Hamilton Anxiety Rating Scale (HARS), Depression Anxiety Stress Scales (DASS-42), and Sentence Completion Test (SSCT). The assessment results indicated that Melati experienced moderate anxiety based on HARS, as well as severe levels of anxiety and depression according to DASS-42. The Cognitive Restructuring intervention, conducted over three sessions, demonstrated positive outcomes in the form of reduced anxiety intensity, increased awareness of irrational thought patterns, and the emergence of more adaptive alternative thoughts and behaviors. These findings highlight the importance of a cognitive approach in addressing anxiety resulting from relational trauma within the context of marriage.